Respiratory care in familial dysautonomia: Systematic review and expert consensus recommendations. (August 2018) - Kazachkov, Mikhail; Palma, Jose-Alberto; Norcliffe-Kaufmann, Lucy; Bar-Aluma, Bat-El; Spalink, Christy L.; Barnes, Erin P.; Amoroso, Nancy E.; Balou, Stamatela M.; Bess, Shay; Chopra, Arun; Condos, Rany; Efrati, Ori; et al.
Abstract: Background: Familial dysautonomia (Riley-Day syndrome, hereditary sensory autonomic neuropathy type-III) is a rare genetic disease caused by impaired development of sensory and afferent autonomic nerves. As a consequence, patients develop neurogenic dysphagia with frequent aspiration, chronic lung disease, and chemoreflex failure leading to severe sleep disordered breathing. The purpose of these guidelines is to provide recommendations for the diagnosis and treatment of respiratory disorders in familial dysautonomia. Methods: We performed a systematic review to summarize the evidence related to our questions. When evidence was not sufficient, we used data from the New York University Familial Dysautonomia Patient Registry, a database containing ongoing prospective comprehensive clinical data from 670 cases. The evidence was summarized and discussed by a multidisciplinary panel of experts. Evidence-based and expert recommendations were then formulated, written, and graded using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) system. Results: Recommendations were formulated for or against specific diagnostic tests and clinical interventions. Diagnostic tests reviewed included radiological evaluation, dysphagia evaluation, gastroesophageal evaluation, bronchoscopy and bronchoalveolar lavage, pulmonary function tests, laryngoscopy and polysomnography. Clinical interventions and therapies reviewed included prevention and management of aspiration, airway mucus clearance and chest physical therapy, viral respiratory infections, precautions during high altitude or air-flight travel, non-invasive ventilation during sleep, antibiotic therapy, steroid therapy, oxygen therapy, gastrostomy tube placement, Nissen fundoplication surgery, scoliosis surgery, tracheostomy and lung lobectomy. Conclusions: Expert recommendations for the diagnosis and management of respiratory disease in patients with familial dysautonomia are provided. Frequent reassessment and updating will be needed. Highlights: Familial dysautonomia (FD) is a rare genetic disease characterized by severe respiratory disorders. A task force performed a systematic review to summarize current knowledge and evidence on respiratory disorders in FD. Expert recommendations for the diagnosis and management of respiratory disease in patients with FD are provided. These recommendations create a milestone in identifying key respiratory issues in patients with FD. It also provides a clinical and research framework to further study respiratory problems in FD.